A Combination of Thematic and Similarity-Based Semantic Processes Confers Resistance to Deficit Following Left Hemisphere Stroke - Kalenine, Solene; Mirman, Daniel; Buxbaum, Laurel J. (Frontiers in Human Neuroscience, 2012)
Semantic knowledge may be organized in terms of similarity relations based on shared features and/or complementary relations based on co-occurrence in events. Thus, relationships between manipulable objects such as tools may be defined by their functional properties (what the objects are used for) or thematic properties (e.g., what the objects are used with or on). A recent study from our laboratory used eye-tracking to examine incidental activation of semantic relations in a word-picture matching task and found relatively early activation of thematic relations (e.g., broom – dustpan), later activation of general functional relations (e.g., broom – sponge), and an intermediate pattern for specific functional relations (e.g., broom – vacuum cleaner). Combined with other recent studies, these results suggest that there are distinct semantic systems for thematic and similarity-based knowledge and that the “specific function” condition drew on both systems. This predicts that left hemisphere stroke that damages either system (but not both) may spare specific function processing. The present experiment tested these hypotheses using the same experimental paradigm with participants with left hemisphere lesions (N=17). The results revealed that, compared to neurologically intact controls (N=12), stroke participants showed later activation of thematic and general function relations, but activation of specific function relations was spared and was significantly earlier for stroke participants than controls. Across the stroke participants, activation of thematic and general function relations was negatively correlated, further suggesting that damage tended to affect either one semantic system or the other. These results support the distinction between similarity-based and complementarity-based semantic relations and suggest that relations that draw on both systems are relatively more robust to damage.